High Endurance Elite Athletes Show Age-dependent Lower Levels of Circulating Complements Compared to Low/Moderate Endurance Elite Athletes - Al-Muraikhy, Shamma; Ramanjaneya, Manjunath; Dömling, Alexander S.; Bettahi, Ilham; Donati, Francesco; Botre, Francesco; Abou-Samra, Abdul-Badi; Sellami, Maha; Elrayess, Mohamed A (Frontiers in Molecular Biosciences, 2021)
Introduction: Aerobic exercise activates the complement system in the peripheral blood. However, the effect of age and high intensity endurance training on the levels of circulating complements and associated inflammatory cytokines, oxidative stress markers and cellular aging remains unknown. Methods: In this study, serum samples from 79 elite athletes who belong to high (n=48) and low/moderate (n=31) endurance sports and two age groups (below 30 years old, n=53, and above 30 years old, n=26) were profiled for 14 complements. Linear models were used to assess differences in complements levels between sport and age groups. Spearmann’s correlation was used to assess the relationship among detected complements and proinflammatory cytokines, oxidative stress markers and telomere lengths. Results: High endurance elite athletes exhibited significantly lower levels of circulating C2, C3b/iC3b and adipsin complements than their age-matched low/moderate endurance counterparts. Levels of C2, adipsin and C3b/iC3b were positively correlated with most detected complements, the pro-inflammatory cytokines TNF-alpha and IL-22 and the anti-oxidant enzyme catalase. However, they were negatively correlated with telomere length only in younger elite athletes regardless of their sport groups. Furthermore, high endurance elite athletes showed significantly lower concentrations of C3b/iC3b, C4b, C5, C5a, C1q, C3, C4, factor H and properdin in younger athletes compared to their older counterparts. Conclusion: Our novel data suggest that high endurance elite athletes exhibit age-independent lower levels of circulating C2, C3b/iC3b and adipsin, associated with lower inflammatory, oxidative stress and cellular aging, as well as lower levels of 10 other complements in younger athletes compared to older counterparts. Assessing the effect of various levels of endurance sports on complements-based immune response provides a better understanding of exercise physiology and pathophysiology of elite athletes.